The earliest Syriac translation of Aristotle's Categories : text, translation, and commentary - Aristotle. (Aristoteles Semitico-Latinus, 2010)
Aristotle's logic first became known in the Middle East through the medium of the Syriac language at a time prior to the rise of classical Arabic philosophy. The present volume makes available for the first time the earliest Syriac translation (sixth century AD) of the Categories, which is here edited together with an English translation, analytical commentary, glossaries and indices. The availability of such an important early work will enable the beginnings of the Semitic Aristotelian tradition to be studied more comprehensively. This will open the way to a better understanding of both the study of Aristotelian logic in Syriac and also of the significance of the Syriac tradition for the genesis and rise of Arabic logic.